2006
DOI: 10.1007/s10488-006-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Project IMPACT: A Report on Barriers and Facilitators to Sustainability

Abstract: Project IMPACT is a collaborative care intervention to assist older adults suffering from major depressive disorder or dysthymia. Qualitative research methods were used to determine the barriers and facilitators to sustaining IMPACT in a primary care setting. Strong evidence supports the program's sustainability, but considerable variation exists in continuation strategies and operationalization across sites. Sustainability depended on the organizations' support of collaborative care models, the availability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 49 publications
2
93
0
1
Order By: Relevance
“…In practice, however, sustaining such collaborative networks can be challenging, particularly given competing demands and constraints on the time and resources of the members of the various organizations in the network [5][6][7][8]. Given the potential risk of investment loss if collaborative network partnerships dissolve before goals can be achieved, researchers are calling for more in-depth studies of "network sustainability" [9,10].…”
mentioning
confidence: 99%
“…In practice, however, sustaining such collaborative networks can be challenging, particularly given competing demands and constraints on the time and resources of the members of the various organizations in the network [5][6][7][8]. Given the potential risk of investment loss if collaborative network partnerships dissolve before goals can be achieved, researchers are calling for more in-depth studies of "network sustainability" [9,10].…”
mentioning
confidence: 99%
“…Other reports have indicated that local context is a key factor in interventions related to primary care management of depression. Blaskinsky et al (2006), observed considerable variation across IMPACT collaborative care intervention sites in operationalization and continuation strategies, and in the barriers and facilitators to sustaining the model. Rollman et al (2006) described two case studies from RWJ's Depression in PC Initiative, in which wide variation in organizational context influenced the implementation of the intervention model, and how each health care system customized the clinical model for local relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Hence it is essential to specify barriers as a prelude to advancing and sustaining service delivery. Corrections can then be made, outcomes evaluated, and services and their providers, improve (Blasinsky, Goldman & Unutzer, 2006;Lee et al, 2007).…”
Section: Nurses and General Practicementioning
confidence: 99%